Carbonate Hydroxyapatite and Silicon-Substituted Carbonate Hydroxyapatite: Synthesis, Mechanical Properties, and Solubility Evaluations - Bang, L.T.; Long, B.D.; Othman, R. (Hindawi Publishing Corporation, 2014)
The present study investigates the chemical composition, solubility, and physical and mechanical properties of carbonate hydroxyapatite (CO3Ap) and silicon-substituted carbonate hydroxyapatite (Si-CO3Ap) which have been prepared by a simple precipitation method. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence (XRF) spectroscopy, and inductively coupled plasma (ICP) techniques were used to characterize the formation of CO3Ap and Si-CO3Ap. The results revealed that the silicate (SiO44−) and carbonate (CO32−) ions competed to occupy the phosphate (PO43−) site and also entered simultaneously into the hydroxyapatite structure.The Si-substituted CO3Ap reduced the powder crystallinity and promoted ion release which resulted in a better solubility compared to that of Si-free CO3Ap. The mean particle size of Si-CO3Ap was much finer than that of CO3Ap. At 750∘C heat-treatment temperature, the diametral tensile strengths (DTS) of Si-CO3Ap and CO3Ap were about 10.8 ± 0.3 and 11.8 ± 0.4 MPa, respectively.